1989
DOI: 10.1111/j.1574-6968.1989.tb03039.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation ofBacillus thuringiensisby electroporation

Abstract: Plasmids were transformed by electroporation into various strains of Bacillus thuringiensis with frequencies of up to 105 transformants/μg. pC 194 transformed all strains tested at a high frequency and cells could be stably transformed with pC194 and pUB110 simultaneously by electroporation with a frequency of 102 pC194 + pUB110 transformant/μg DNA. Low transformation frequencies observed with some plasmids, especially those grown initially in Escherichia coli, could be increased by passage through B. thuringi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…A brief electric pulse is given which causes a disruption of the lipid bilayer, resulting in the formation of aqueous pores in the membrane. Diverse protocols for transformation of B. thuringiensis using electroporation were published independently in the same year (Bone and Ellar 1989;Lereclus et al 1989;Mahillon et al 1989;Masson et al 1989;Schurter et al 1989). These studies showed that the transformation efficiency varies depending on the recipient strain, which may reflect differences in the restriction/modification systems of the strains.…”
Section: Transformation Of Bacillus Thuringiensismentioning
confidence: 98%
See 1 more Smart Citation
“…A brief electric pulse is given which causes a disruption of the lipid bilayer, resulting in the formation of aqueous pores in the membrane. Diverse protocols for transformation of B. thuringiensis using electroporation were published independently in the same year (Bone and Ellar 1989;Lereclus et al 1989;Mahillon et al 1989;Masson et al 1989;Schurter et al 1989). These studies showed that the transformation efficiency varies depending on the recipient strain, which may reflect differences in the restriction/modification systems of the strains.…”
Section: Transformation Of Bacillus Thuringiensismentioning
confidence: 98%
“…thuringiensis produces parasporal crystal proteins during sporulation whose genes are typically located on large plasmids (Schnepf et al 1998). These genes have been cloned and genetically engineered to improve their insecticidal activity due that it has been developed efficient cloning vectors and transformation systems for B. thuringiensis (Bone and Ellar 1989;Lereclus et al 1989;Mahillon et al 1989;Masson et al 1989;Schurter et al 1989).…”
Section: Shuttle Vectors Of Bacillus Thuringiensismentioning
confidence: 99%
“…Bcrcillcls species that have been IAuthor to whom all correspondence should be addressed. successfully electrotransformed include Bacillus umyloliquefacier~s (Vehmaanpera 1989), Bacillus ar~thr.acis (Dunny et al 1991), Bacillus brevis (Takagi et al 1989), Bacillus sclbtilis (Brigidi et al 1990), Bacilllrs cereus (Belliveau and Trevors 1989;Schurter et al 1989), Bacillus sphaericus (Taylor and Burke 1990), Bacillus circulans (Li Yuan and Wong 1984), and Bacillus tlzur-irzgiensis (Bone and Ellar 1989;Mahillon et al 1989). The technique basically involves subjecting a cellular suspension to a short-duration, high-amplitude electrical pulse resulting in the reversible permeabilization of the cellular membrane, which allows entry of exogenous DNA into cells .…”
Section: Introductionmentioning
confidence: 96%
“…A 2.75 kb BgflI-XbaI fragment that contained an altered cryZVA gene was excised from the replicative form DNA of a mutagenesis derivative of MIS278, was substituted for the BglII-XbaI segment of cryZVA in pIS422, and the mutation sites were re-confirmed by sequencing. The pIS422 mutants were introduced into HD522 C37-21 by electroporation [17].…”
Section: Construction Ofplasmidsmentioning
confidence: 99%